A Secure Cloud Server Using Raspberry Pi and Kerberos Authentication Protocol - Ansari, Ahlam; Ansari, Tahir; Hingora, Faizan; Ansari, Mudassir (International Journal of Computer Sciences and Engineering, 2015)
An internet based computing where number of servers situated remotely are inter-connected to each other and access to some services are allowed online is framed as Cloud Computing. But the existing systems require very expensive hardware and the power consumption is also high. Also the existing systems are quite complex and usually require larger area to install along with high maintenance cost. So the idea is to propose a system where users can store their data over the cloud and retrieve their data from any part of the world. The proposed system not only provides reliable file storage but also provides high security. This proposed system uses Raspberry Pi which is a single-board computer; small in size to develop a cloud server which will be secured as well as less expensive. For security, the proposed system uses Kerberos authentication protocol which will act as a third-party service that will be used to authenticate the user’s identity. It will act as a bridge between the user and the cloud storage.